Technological Development in the Era of Digitalization in Islamic Education - Fi’liyah, Ma’rifatul (Maliki Interdisciplinary Journal, 2024)
This study examines the development of technology in the era of digitalization and its impact on Islamic education. The era of digitalization has brought significant changes in various aspects of life, including the education sector. Information and communication technology (ICT) provides new opportunities in teaching, learning, and education administration management methods. In the context of Islamic education, the use of modern technology can increase accessibility to learning resources, enrich teaching materials, and facilitate interaction between teachers and students. The study also highlights the challenges faced, such as the digital divide and the need for adequate digital literacy among educators and learners. Through qualitative analysis, this study concludes that the integration of technology in Islamic education not only increases the effectiveness of the learning process, but also strengthens the understanding and practice of Islamic values in the digital era.